1988
DOI: 10.1161/01.hyp.11.1.78
|View full text |Cite
|
Sign up to set email alerts
|

Effects of thyroid function on blood pressure. Recognition of hypothyroid hypertension.

Abstract: SUMMARY Hypothyroid ism has been known to be associated, at times, with diastolic hypertension. We have found in 40 thyrotoxic patients that the induction of hypothyroid ism by radioiodine therapy significantly increased diastolic blood pressure, raising it above 90 mm Hg in 16 (40%) of the patients. Restoration of euthyroidism with thyroxine administration significantly reduced the systolic and diastolic blood pressures in these patients, with a fall in diastolic pressure below 90 mm Hg in nine of 16 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
58
0
2

Year Published

1990
1990
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 141 publications
(60 citation statements)
references
References 18 publications
0
58
0
2
Order By: Relevance
“…Our findings are in concordance with previous work studying non-referred individuals 13,14 but contrast with reports from specialty clinics. [2][3][4][5][6] In our earlier cross-sectional study of post-menopausal women at a primary care office no association between hypothyroidism and hypertension was detected. 14 The second negative study was community-based and compared 81 hypothyroid women to 73 euthyroid women drawn from the surrounding community.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…Our findings are in concordance with previous work studying non-referred individuals 13,14 but contrast with reports from specialty clinics. [2][3][4][5][6] In our earlier cross-sectional study of post-menopausal women at a primary care office no association between hypothyroidism and hypertension was detected. 14 The second negative study was community-based and compared 81 hypothyroid women to 73 euthyroid women drawn from the surrounding community.…”
Section: Discussionmentioning
confidence: 72%
“…TSH was forced to remain within the regression model became hypothyroid following treatment with radioiodine. 3 Sixteen (40%) of these patients also developed hypertension but after receiving thyroid replacement nine of the 16 (56%) returned to a normotensive condition. These studies lacked control groups and it is possible that some of the individuals were demonstrating a placebo effect.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Thus, in a study by Streeten et al 20 on 688 hypertensive subjects the prevalence of hypothyroidism was 3.6%. Similarly, Gumieniak et al 5 found significantly higher serum TSH levels and significantly Blood pressure and TSH A Iqbal et al lower free T 4 index in 194 hypertensive subjects as compared with 90 normotensive subjects.…”
Section: Discussionmentioning
confidence: 91%